Effective Communication of System-Level Events for Hospital System Health and Nurse Well-Being: A Qualitative Study - Angela C. Brittain; Jane M. Carrington (Safety)
Many injuries and deaths occur yearly in the United States due to preventable errors; however, documented harm is lower in hospitals with Magnet® designation from the American Nurses Credentialing Center (Silver Spring, MD, USA). This manuscript illustrates insights from Magnet® and non-Magnet® nurses and nursing leaders regarding what impacts hospital system health, how those factors are communicated, and how hospital system health impacts patient safety. A qualitative descriptive approach was used with semi-structured interview questions. Within-methods data triangulation was applied to transcribed interviews using thematic analysis, application of the Goodwin statistic, and natural language processing (NLP). Thematic analysis revealed the four main themes of Healthy Systems, Unhealthy Systems, Patient Safety, and Nurse Well-Being. NLP revealed non-Magnet® leaders and nurses scored highest for anxiety, anger, and sadness, in contrast to Magnet® participants who had the highest levels of positive emotion. Key findings from the Magnet® participants revealed that poaching employees and placing people in the wrong positions harm hospital system health and patient safety. The use of within-methods data triangulation illuminated the contextual depth of the participants’ speech, revealing the alarming emotional state that non-Magnet® nurses and leaders are facing. Healthcare staff’s wellness must be prioritized to cultivate environments that provide safe care.